A comparison of two crystals of 6, 13-bis (tri-isopropylsilylethynyl) pentacene (TIPS-pentacene) prepared for organic field effect transistors (OFETs). (July 2015) - Murtaza, Ghulam; Ahmad, Ishtiaq; Wu, Jiake
Graphical abstract: Highlights: We have prepared the single crystals by Droplet Pinned Crystallization (DPC) Method. We observe the degradation of mobility at different gate voltages. Degradation in mobility is due to the presence of shallow/deep traps which are the cause of ohmic loss. Mobility depends on morphology of the grown single crystal monolayer. Crystallinity plays an important role in the mobility. Abstract: We report on the comparative study of two single crystals grown for organic field effect transistors having different concentration, contact step height, surface roughness and crystallinity of single crystals prepared by droplet pinned crystallization (DPC) method. Organic Field-Effect Transistors (OFETs) consisting of 6,  13-bis (tri-isopropylsilyl-ethynyl) pentacene (TIPS-pentacene) as active semiconducting layer are fabricated. The concentration range of TIPS-pentacene is taken from 0.2 mg/ml to 1.0 mg/ml but for the detailed study, OFETs with concentration of 0.2 mg/ml and 0.6 mg/ml are selected. Five devices for each concentration are fabricated by varying contact positions whereas the top drain and source contacts are made of gold. The calculated values of the threshold voltage, sub threshold slope, Number of interface traps and the saturation mobility of TIPS-pentacene having concentration 0.2 mg/ml are in the range from −12 V to 13 V, −16 (V/decades) to −30 (V/decades), 1.67 × 10 12  cm −2  eV −1 to 3.13 × 10 12  cm −2  eV −1 and 0.2 to 1.1 cm 2 /V s while the values for the concentration 0.6 mg/ml are −22 V to 2.6 V, −17 (V/decade) to −22 (V/decade), 1.77 × 10 12  cm −2  eV −1 to 2.29 × 10 12  cm −2  eV −1 and 2.0–2.2 cm 2 /V s. The mobility degradation of TIPS-pentacene is found at different gate voltages.